Islamic environmental reporting and news sources in Malaysian newspapers - Mohamad Saifudin Mohamad Saleh; Sharafa Dauda; Tan, Kwang Shean; Nik Norma Nik Hasan (Penerbit Universiti Kebangsaan Malaysia, 2022)
Islamic environmental reporting is getting its toll worldwide including in Malaysia. News on Islamic environmental research on environmental journalism and news sources in Malaysia exist but the role of news sources on Islamic environmental news are largely unknown. Therefore, this study examines the roles of news sources and journalists in Islamic environmental news coverage in Malaysia, a country with an Islamic-oriented news media. By analysing the content of news articles and interviewing journalists at two mainstream Malaysian newspapers (Utusan Malaysia and Berita Harian), this study found that news sourcing judgements at Utusan Malaysia compromised western and Islamic news values of public interest by preferring sources with knowledge on environmental issues rather than sources with Islamic knowledge; while Berita Harian cited more sources related to Islam. Arguably, preference for sources with Islamic knowledge in reporting Islamic environmental news serves readers’ interest best and will guarantee audience rights and interests.